Predictive factors of anxiety level in postpartum period - Soudabeh Niroomand; Fatemeh Razavinia; Zeynab Bayat; Mahsa Jafari; Farahnaz Rostami; Samaneh Youseflu (Zanjan University of Medical Sciences and Health Services, 2019)
Background: Pregnancy and delivery are considered as pleasant physiological phenomena. This period, however, sometimes leads to variable mood states in women and makes them more sensitive to psychological stimuli and problems. Objectives: The present study aimed to investigate the role of breastfeeding, type of delivery, contraceptive method, planned pregnancy, and history of infertility on the anxiety level of Iranian women who referred to health centers in Zanjan in the postpartum period. Methods: This cross-sectional study was conducted on 420 women who attended the health care centers in Zanjan city, Iran, during 2018-2019. A checklist including questions about demographic and reproductive information and Beck anxiety inventory were used as the data collection instruments. The data were analyzed using SPSS 21 software through regression analysis. Results: This study found that the history of infertility (β=0.26, t=9.38, p<0.001), unplanned pregnancies (β=0.23, t=-7.00, p<0.001), exclusive breastfeeding (β=-0.47, t=-17.40, p<0.001), mothers' education (β=-0.08, t=-2.89, p<0.001), DMPA (β=0.23, t=6.62, p<0.001), and withdrawal (β=0.17, t=4.59, p<0.001) contraception method were associated with anxiety level. Conclusion: The results of the present study indicate that factors such as breastfeeding, contraceptive methods, infertility history, unplanned pregnancy, and educational level influence womenchr('39')s anxiety level in postpartum period. Identifying and screening women with high levels of anxiety and providing proper counseling to these mothers can help improve their health, infants, families, and community